2003
DOI: 10.1096/fj.02-0352rev
|View full text |Cite
|
Sign up to set email alerts
|

Reappraisal of serum starvation, the restriction point, G0, and G1 phase arrest points

Abstract: The restriction point in the G1 phase of the mammalian cell cycle is the oldest, best-known, and widely accepted control point regulating division cycle in mammalian cells. Origins of the restriction point and its subsequent history are reanalyzed here. The initial proposal of the restriction point has an alternative explanation, which is that cells arrested with a G1 phase amount of DNA can arise from the inhibition of a process or processes occurring throughout the cell cycle and are not restricted to any pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
113
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 136 publications
(117 citation statements)
references
References 31 publications
3
113
0
1
Order By: Relevance
“…We observed that about 10% of PRL-3-expressing cancer cells could take up antibodies in culture, and this uptake was enhanced 6-fold upon serum starvation (22). Serum starvation is used to arrest cells at G 1 and G 0 phases (23). It is possible that particular stages (perhaps G 1 -G 0 ) of the cell cycle contribute to the ability of cells to take up the antibodies.…”
Section: Possible Mechanisms For Antibody Targeting Of Intracellular mentioning
confidence: 94%
“…We observed that about 10% of PRL-3-expressing cancer cells could take up antibodies in culture, and this uptake was enhanced 6-fold upon serum starvation (22). Serum starvation is used to arrest cells at G 1 and G 0 phases (23). It is possible that particular stages (perhaps G 1 -G 0 ) of the cell cycle contribute to the ability of cells to take up the antibodies.…”
Section: Possible Mechanisms For Antibody Targeting Of Intracellular mentioning
confidence: 94%
“…Serum deprivation of cells is known to alter the expression of several genes that are involved in cell proliferation and differentiation (Mandl et al, 2007;Muise-Helmericks et al, 1998). Serum starvation typically causes cell cycle arrest (G0 arrest or quiescence) eventually leading to senescence, apoptosis or cellular differentiation (Alexandre et al, 2000;Cooper, 2003;Simm et al, 1997). Interestingly, upon serum starvation, the number of GRC-RNA foci within the nuclei was dramatically decreased (5-8 instead of 50-60) but the existing nuclear foci became larger and more prominent (Fig.…”
Section: Grc-rna Nuclear Foci Number Is Altered During Cell Differentmentioning
confidence: 99%
“…It is generally believed that serum-starved cells are arrested in G 1 or G 0 phase, with most of the genes functioning at their basal expression level (53)(54)(55). However, there are some reports showing that serum starvation leads to up-regulation of certain genes.…”
Section: Transcriptional Regulation Of Sirp␣1 By Egfr Signalingmentioning
confidence: 99%